A responsabilidade socioambiental empresarial em face dos desastres ambientais: a lama de Mariana-MG (um estudo de caso) - (:unkn) unknown (Universidade Brasil, 2020)
This work deals with corporate social and environmental liability, focusing on the disaster that occurred in city of Mariana, Minas Gerais, in 2015, after the fateful rupture of a mining tailings dam, which belonged to the mining company Samarco Mineração S.A., controlled by Vale S.A. and BHP Billiton Brasil Ltda. This research motivates, besides the current theme, the social interest in the analysis of corporate social and environmental liability, regarding the articulation between the social responsibility project and its implementation or not, in the face of current environmental disasters. Through bibliographic research and case study, this paper aims to analyze corporate social liability and its consequences in the episode of Mariana. Noteworthy is the rupture of the Fundão dam as an example of corporate social irresponsibility, considering that the tragedy in Mariana was not due to adverse causes or forces of nature, but due to recklessness and lack of security. It is also noted that although the environmental disaster has caused several negative consequences such as the death of people, destruction of communities, silting up of water courses, perishing of species of fauna and flora and still putting communities in conditions of vulnerability, the Mariana's local population does not want business activities to end.
Keywords: Dano ambiental; Barragem de minério; Mineração; Rejeitos minerais; CB